The role of the social worker in rehabilitating women and children in the `Tsunami tragedy' - Sultgana, A. Shahin; Shanmugavelayutham, K. (2005)
The Tsunami has left hundreds of traumatised victims in its wake. such victims require the services of professional social workers and counsellors to help them cope with their tragedy and go on with life. Teams of counsellors have already started work in the Tsunami affected areas. - Reproduced.
Keywords: Tsunami; Children; Women; Rehabilitation; Social workers